Effects of Physical Exercises in Asthma: An Umbrella Review of Systematic Review and Meta‐Analysis - Fuchun Huang; Shuang Yang; Mingxuan Ma; Jialin Zhang; Hua Liu (The Clinical Respiratory Journal)
ABSTRACT Background As a disease‐modifying strategy, physical exercise has been demonstrated to significantly improve quality of life, exercise capacity, and lung function in individuals with asthma. However, the quality and robustness of this evidence has not been thoroughly examined in many large‐scale investigations. In order to assess the evidence addressing the effects of physical exercise in patients with asthma, we therefore carried out an umbrella review. Methods A comprehensive search of the PubMed, Web of Science, and Cochrane databases for systematic reviews and meta‐analyses of the effects of physical activity on asthma was conducted up to December 31, 2022. The study was registered in Prospero (CRD42023382921). For every qualified systematic review and meta‐analysis, we extracted information on the main characteristics and general findings. The GRADE tool was utilized to quantify the strength of the evidence, and the AMSTAR2 score was employed to evaluate the methodological quality. Results A total of 1254 articles were searched, and 42 independent results were identified as eligible in the 11 articles that were included. Of the 42 unique outcomes, two were rated as high, two as medium, and the rest as low or very low. Physical exercise is beneficial for improving QoL, exercise capacity, and lung function in patients with asthma. Conclusions According to our research, physical activity benefits QoL of patients with asthma, exercise tolerance, and lung function. In the future, further evidence from superior prospective studies will be required because the quality of the available evidence is now insufficient.